Local Identity Vernacular Rowhouse in Floating Markets Central Region - Sonthichai, Supachock; Anongchai, Lakkana (Journal of Building Energy & Environment, 2021)
In this research, Local identity Vernacular Rowhouse in Riverine of survey Research into the area to explore the Vernacular Rowhouse around the Floating markets central region of 2 area group.(Floating markets central region Rowhouse east and Rowhouse west) and select indigenous houses in each ethnic group. From the study of the physical area of the geography that settled the Riverine society in 1707-1932. Explain the relationship between the cultural landscape context and the cultural context to through the transition period Under the characteristics of the river basin society on both sides of the east is Ban Mai Floating Market Chachoengsao Province and west side is Amphawa Floating Market Samut Songkhram Province. Remains the same old identity from the Chinese cultural context inherited from ancestors in the form of kinship system and appears the local architectural wisdom that is communicated through houses around the floating market area in the characteristics of Cultural context in Riverine society of Transferability cultural.